Devario xyrops, a new species of danionine fish from south-western Myanmar (Teleostei: Cyprinidae) - Fang, Fang; Kullander, Sven O. (Zootaxa, 2009)
Devario xyrops is described from small rivers on the western slope of the Rakhine Yoma in south-western Myanmar. It is distinguished from all other species in the genus except D. anomalus by its colour pattern including a dark blotch or condensed series of vertical bars anteriorly on the side, separate from a posterior dark horizontal band; and distinguished from D. anomalus in particular by deeper body (29.9–35.8% SL, vs. 25.0–26.8 % SL) and fewer lateral line scales (31–33, modally 32 vs. 33–35, modally 34).